analisis Pengaruh Kepemimpinan Pelayan Dan Lingkungan Pelayanan Terhadap Motivasi Melayani Dan Komitmen Pelayanan - Fonataba, Jongky Robertho (Universitas Sam Ratulangi, 1996)
A good leader is a leader who is able to develop the organization and a leader who is able to provide a good service, can protect its subordinates, as well as giving themselves more active in the work. Based on the research results obtained the following conclusions (1) The influence of Leadership waiter variable (X1) to variable Motivation Serve (Y1) is not significant. (2) The influence of Environmental Services variables (X2) to variable Motivation Serve (Y1) is significant. (3) The influence of Variable Leadership waitress (X1) Variable Commitment to Care (Y2) is significant. (4) The influence of Environmental Services (X2) to Variable Service Commitment (Y2) is not significant. (5) The influence of Variable Motivation Serve (Y1) to Variable Service Commitment (Y2) is significant Keywords: Leadership waitress, Environmental Services, Serving Motivation, commitment to service, church